Astaxanthin Protects PC12 Cells against Homocysteine- and Glutamate-Induced Neurotoxicity - Chang, Chi-Huang (Molecules, 2020)
Memory impairment has been shown to be associated with glutamate (Glu) excitotoxicity, homocysteine (Hcy) accumulation, and oxidative stress. We hypothesize that Glu and Hcy could damage neuronal cells, while astaxanthin (ATX) could be beneficial to alleviate the adverse effects. Using PC12 cell model, we showed that Glu and Hcy provoked a huge amount of reactive oxygen species (ROS) production, causing mitochondrial damage at EC(50) 20 and 10 mm, respectively. The mechanisms of action include: (1) increasing calcium influx; (2) producing ROS; (3) initiating lipid peroxidation; (4) causing imbalance of the Bcl-2/Bax homeostasis; and (5) activating cascade of caspases involving caspases 12 and 3. Conclusively, the damages caused by Glu and Hcy to PC12 cells can be alleviated by the potent antioxidant ATX.